The Impact of Fluctuations on Some Macroeconomic Variables in the Libyan Economy: GDP- Inflation. - بدر حسن (Dirasat in Economics and Business, 2020)
The main objective of this research was to investigate whether there is an impact of oil price fluctuations on the GDP and inflation in the Libyan economy during the period 1980-2010 in the short run and long run. For this purpose, the research used the tests and methods of the modern quantitative standard approach, As a root and unit test and co integration test and the error correction model, The results showed that there is a negative impact of oil price fluctuations on output in short run, This effect is positive in the long run, The results also showed that there is no impact of oil price fluctuations on inflation.